2021
DOI: 10.1121/10.0003501
|View full text |Cite
|
Sign up to set email alerts
|

Generative adversarial networks for the design of acoustic metamaterials

Abstract: Metamaterials are attracting increasing interest in the field of acoustics due to their sound insulation effects. By periodically arranged structures, acoustic metamaterials can influence the way sound propagates in acoustic media. To date, the design of acoustic metamaterials relies primarily on the expertise of specialists since most effects are based on localized solutions and interference. This paper outlines a deep learning-based approach to extend current knowledge of metamaterial design in acoustics. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(34 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Several studies focused on discriminative and generative design methods have shown excellent performance beyond the human capability. [18][19][20] Meng et al presented a linear sampling method (LSM) with neural networks to reconstruct the shape of obstacles with acoustic far-field data. [21] LSM relies on selecting a contour line to obtain the shape information of an object.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies focused on discriminative and generative design methods have shown excellent performance beyond the human capability. [18][19][20] Meng et al presented a linear sampling method (LSM) with neural networks to reconstruct the shape of obstacles with acoustic far-field data. [21] LSM relies on selecting a contour line to obtain the shape information of an object.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, this gap is minimized using empirical trial-and-error methods in conjunction with prior domain knowledge. With technological advancements and increased computational power, efficient optimization algorithms and data-driven techniques, such as machine learning (ML) are employed to automate the learning process while utilizing physics-based understanding (Bacigalupo et al 2020;Donda et al 2021;Ahmed et al 2021;Sun et al 2021;Gurbuz et al 2021;Zheng et al 2020;Wu et al 2021;Bianco et al 2019;Wu et al 2022) through physical models.…”
Section: Introductionmentioning
confidence: 99%
“…The key distinctions of DDMD against conventional approaches are that (i) DDMD can accommodate domain knowledge (in both dataset and model) with topologically free design variation; (ii) it has little restrictions on analytical formulations of design interest; (iii) some of DDMD enables iteration-free design, which pays off the initial cost of data acquisition and model construction. Capitalizing on the advantages, DDMD has reported a plethora of achievements in recent years from diverse domains [1,8,9,10,12,13,14].…”
Section: Introductionmentioning
confidence: 99%